An Analysis of Ogba Derivational Affixes - Nwokoji, Chukwuemeka (NIU Journal of Humanities, 2024)
This study describes the analyses of derivational affixes in Ọgba Language. It particularly examines the derivational operations (role) of affixes in the Language. It shows how certain grammatical ideas or notions like reduplication, prefixation and suffixation, interfixation, prefix and miscellaneous coinages and derivative tone are marked by affixes in Ọgba. Some of the derivative affixes (morphemes) in the language used to arrive at this are as follow: e̩, a, I, o, o̩, u, m, n marking different coinages. Other linguistics processes affected by morphological operations in the language include the derivation of the noun and verb with interfix; coping the consonant of the verb root to construct partial reduplication and tone as derivative morphemes. We believe that this research work would be significant in the development of the Ọgba language, and most pertinently, increase the zeal for the preservation of the language in Rivers State and Nigeria in general.